Pola Asuh Islami pada Anak Usia Dini dalam Buku Cara Rasulullah Saw Mendidik - Riska Nofianti, Farhati; Fauzi; Nur Hafidz (Generasi Emas, 2023)
Parenting patterns in the family occur because of the parents' educational activities. Parenting style plays an important role in children's growth and development. The aim of the concept of parenting is also found in the book How the Prophet SAW Educated Children by Ayu Agus Riani which is the material object of this research. For this reason, this research aims to find and explain the concept of Islamic parenting patterns contained in the book How the Prophet SAW Educated Children by Ayu Agus Riani. This research method is a qualitative method in library research by reflecting the ideas in the books being studied. The analysis technique uses data reduction, data clarification and data verification. The results of this research are that Islamic parenting is child education in the family which is based on the Koran and al-Hadith. From here, Islamic parenting in the book How the Prophet SAW Educated Children by Ayu Agus Riani will discuss exemplary attitudes, advising, being fair, fulfilling children's rights, praying for, guiding children, and avoiding insults and insults at children.